METTL5 regulates SEPHS2-mediated selenoprotein synthesis to promote multiple myeloma survival and progression - Junyao Jiang; Fangmin Zhong; Zuomiao Xiao; Fangyi Yao; Jing Liu; Meiyong Li; Huan Zeng; Yuxiang Qiu; Jing Zhang; Haibin Zhang; Shuqi Li; Ting huang; et al. (Cell Death and Disease)
Abstract The abnormal expression of m6A methyltransferase is a significant factor in the occurrence and progression of tumors. The 18S ribosomal RNA (rRNA) m6A methyltransferase Methyltransferase-like 5 (METTL5) is upregulated in various cancers, leading to adverse prognosis by abnormally regulating protein translation in tumor cells. However, the functionality and molecular mechanisms of METTL5 in the progression of multiple myeloma (MM) remain unknown. In this study, we demonstrate that the expression of METTL5 in the bone marrow (BM) of newly diagnosed MM patients is significantly higher than in healthy individuals and patients in remission following treatment. Importantly, we found that MM patients with upregulated METTL5 expression had a poorer prognosis. Additionally, we show that METTL5 plays a key role in promoting MM progression both in vitro and in an orthotopical xenograft model. Mechanistically, the depletion of METTL5 expression mediates a decrease in overall translation efficiency and selenium metabolism-related signaling pathway levels. We further revealed that the reduction in selenophosphate synthetase 2 (SEPHS2) translation efficiency mediated by METTL5 depletion can lead to diminished synthesis of selenoproteins and increased reactive oxygen species (ROS), thereby inducing apoptosis in MM. Salvianolic acid C (SAC) was identified as a potential METTL5 inhibitor, demonstrating significant pro-apoptotic effects during the treatment of MM both in vitro and in vivo. In summary, our research highlights the critical role of METTL5 in the progression of MM cells. Our data indicate METTL5’s function is to influence the overall translation efficiency and reprogram selenium metabolism to inhibit apoptosis. Therefore, SAC may be an ideal candidate drug for suppressing MM progression.